Assessment of fertility and reproductive potential in the arctic regions of the Russian Federation from 2014 to 2023 - E. D. Mayskaya; T. M. Duryagina; A. N. Smolinets; M. D. Sukharev; A. L. Sannikov; A. G. Kalinin (Translational Medicine, 2026)
Background. Assessment of the reproductive potential of the subarctic territories of Russia is of high significance due to the specific climatic, geographical, socio-economic and ethno-demographic conditions that affect fertility. Despite national demographic trends, regional variability in fertility rates, infertility, reproductive behaviour and accessibility of assisted reproductive technologies remains insufficiently studied, which limits the development of targeted management decisions. Aim. To conduct a comprehensive assessment of fertility and reproductive potential in the subarctic regions of the Russian Federation (Murmansk and Arkhangelsk regions, Chukotka, Yamalo-Nenets, Khanty-Mansiysk and Nenets autonomous okrugs, Republics of Karelia, Komi and Sakha (Yakutia), Krasnoyarsk Krai) over the period 2014–2023, based on a system of demographic and medico-statistical indicators. Materials and methods. Data from official statistics (Rosstat, Federal State Statistics Service, fedstat. ru) as well as information from the State Budgetary Institution “Research Institute of Healthcare Organization and Medical Management of Moscow Health Department” were used. The following indicators were analysed: proportion of women of fertile age, crude birth rate and total fertility rate (TFR), including age-specific rates for groups 15–19, 20–24, 25–29 and 30–49 years; proportion of indigenous population; newly diagnosed and total infertility rates among men and women of fertile age; proportion of successful IVF cycles; abortion rate; maternal mortality rate; and numbers of marriages and divorces. Descriptive statistics, cluster analysis (by mean TFR) and Pearson’s correlation analysis were applied. Results. The median TFR over the 10-year period for the Russian Federation was 1.6. In the subarctic regions, values varied: cluster analysis identified three groups – with high (Nenets Autonomous Okrug, Yamalo-Nenets Autonomous Okrug, Republic of Sakha (Yakutia)), medium (Khanty-Mansiysk Autonomous Okrug, Chukotka Autonomous Okrug, Republic of Komi, Krasnoyarsk Krai) and low (Arkhangelsk Region, Republic of Karelia, Murmansk Region) fertility levels. Correlation analysis revealed the strongest statistically significant associations of TFR with the proportion of women of fertile age (r=0.84) and the proportion of indigenous peoples (r=0.79). The influence of infertility rates and abortion frequency on TFR variation in the studied sample was weak and not statistically significant. Conclusion. Interregional differences in fertility within the subarctic zone are primarily determined by structural (age and ethnic) factors rather than by medico-reproductive losses (infertility, abortions). The obtained results indicate the need for further in-depth analysis incorporating socio-economic and migration factors to substantiate regional demographic policy.